(untitled) (Revista INTEREDU11, 2021)
This article gives an account of a reflective process about the relationship between curriculum, the Chilean school system and teachers. How curriculum is conceptually understood is firstly determined from its realization levels to the curriculum designing processes developed in Chile. Along with the latter, the Chilean basis curriculum design is deepened by specifying its main components and organization of formal curriculum. Then a relationship is established and a reflection is done on the curriculum and function of teachers in specific contexts where they must perform their job professionaly. Some recommendations about teaching duty conclude this work specifically regarding influence and understanding of curriculum both for teaching professional practice and for the decision –taking level on how, what and when to teach and assess in contexts of teaching procedures.